2010
DOI: 10.1007/s00122-010-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

The genetic control of tolerance to aluminum toxicity in the ‘Essex’ by ‘Forrest’ recombinant inbred line population

Abstract: Aluminum (Al) toxicity to plant roots is a major problem of acidic soils. The main chemical reaction involved is Al hydrolysis. Application of lime or nitrate fertilizers to raise soil pH reduces Al toxicity but not as economically as a plant genotypes with natural tolerance against this stress. Ammonium fertilization of crops and assimilation of ammonium (even that derived from dinitrogen) are particularly acidifying of the root zone. The aims of the present study were to find genotypes of soybean tolerant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Sharma et al [48] identified two major QTL for tolerance to Al. These two QTL were also detected in the present study and were located in the marker intervals satt160-satt252 (F) and satt202-satt371 (C2), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al [48] identified two major QTL for tolerance to Al. These two QTL were also detected in the present study and were located in the marker intervals satt160-satt252 (F) and satt202-satt371 (C2), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple QTL with major and minor effects have been reported to control Al resistance in Arabidopsis (Hoekenga et al., 2003; Kobayashi & Koyama, 2002; Kobayashi, Furuta, Ohno, Hara, & Koyama, 2005), sorghum [ Sorghum bicolor (L.) Moench] (Magalhaes et al., 2004), rice ( Oryza sativa L.) (Nguyen et al., 2002), maize ( Zea mays L.) (Ninamango‐Cardenas et al., 2003), and soybean [ Glycine max (L.) Merr.] (Bianchi‐Hall et al., 2000; Korir, Zhang, Wu, Zhao, & Gai, 2013; Sharma, Sharma, & Lightfoot, 2011). Genetic variation in Al resistance has been reported in common bean (Blair, Lopez‐Marin, & Rao, 2009; Butare et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation lies on NH4NO3-N applications. The increase in soil acidity with the use of ammoniacal fertilizers is caused by the nitrification process, the oxidation of NH4 + to NO3releases H + protons, which occupy cation exchange sites leached with NO3 -, reducing the soil pH [27,28]. The high values of Al 3+ observed in N fertilized treatments also match with lower pH values.…”
Section: Soil Chemical Indicatorsmentioning
confidence: 99%
“…Liming has long been reported as an efficient way to reduce soil acidity in both conventional and NT systems [8,9]; this fact was observed in the treatments with liming as Oat-L and Oat-NL in which the soil pH increased and, consequently, the Al 3+ contents were lower. Increasing soil pH with liming favors a reductions in Al 3+ content due to its precipitation as Al(OH)3 [28].…”
Section: Soil Chemical Indicatorsmentioning
confidence: 99%